Cyclic Nucleotide Phosphodiesterases (PDEs): Diverse Regulators of Cyclic Nucleotide Signals and Inviting Molecular Targets for Novel Therapeutic Agents - Manganiello, V. C.; Degerman, E. (Thrombosis and Haemostasis, 1999)
Cyclic adenosine 3’5’-monophosphate (cAMP) and cyclic guanosine 3’5’-monophoshpate (cGMP) are critical intracellular second-messengers involved in the transduction of a wide variety of extracellular stimuli, including peptide hormones, growth factors, cytokines, neurotransmitters and light. These messengers modulate many fundamental biological processes, including growth, differentiation, apoptosis, glycogenolysis, lipolysis, immune/inflammatory responses, etc.By catalyzing hydrolysis of cAMP and cGMP, cyclic nucleotide phosphodiesterases (PDEs) are important determinants in regulating the intracellular concentrations and, consequently, the biological actions of these second-messengers (Fig. 1). The advent of molecular genetics has revealed the extraordinary complexity and diversity of the mammalian PDE superfamily, which contains at least 10 highly regulated and structurally-related gene families (PDEs 1-10).1-8 As depicted in Figure 1, some PDEs are highly specific for hydrolysis of cAMP (PDEs 4,7,8), some are cGMP-specific (PDEs 5,6,9), and some exhibit mixed specificity (PDEs 1,2,3,10). Most gene families are comprised of more than one isogene (indicated by A-D in Table 1). At least 19 genes encoding more than 30 isoforms have been identified. PDE families differ with respect to their primary structures, sensitivity to specific inhibitors, tissue distribution, subcellular localization, and mechanisms of regulation (Table 1).2-6 Within individual families, different mRNAs are generated from the same gene by use of different transcription initiation sites or by alternative mRNA splicing. These variant PDE isoforms are often tissue-specific and selectively expressed in various tissues and cell types.2-6 The importance of cyclic nucleotide signaling in cell regulation and the molecular diversity of PDEs has presented targets for selective interventions and development of family-specific PDE inhibitors as therapeutic agents. This brief review will discuss some general characteristics of PDEs and then focus on the cellular biology and diverse functions of different PDE isoforms and their potential as therapeutic targets.